2018
DOI: 10.2514/1.j056113
|View full text |Cite
|
Sign up to set email alerts
|

Slat Noise from an MD30P30N Airfoil at Extreme Angles of Attack

Abstract: This study investigates the slat noise of a two-dimensional scaled, unswept, and untapered MD30P30N high-lift model. The experimental data refer to aeroacoustic and aerodynamic measurements in a closed-section wind tunnel for a wide range of angles of attack (from −6 deg up to the stall; approximately at 18 deg) and Mach numbers between 0.07 and 0.1. Three slat configurations (the original MD30P30N, another with a higher slat deflection, and one with smaller slat gap and overlap) are studied experimentally. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…For cases olBα4 and olCα4, the agreement is within 5 dB Hz −1 . The reduction of the low-frequency slat noise with increasing angle of attack captured by the present simulations agrees with previous results in the literature (Dobrzynski & Pott-Pollenske 2001;Kolb et al 2007;Imamura et al 2009;Amaral et al 2017). Low-frequency sound amplitude, especially for the narrowband peaks, is reduced as the overlap is increased, to the point that the peaks are not observed for the largest overlap simulated, olCα4.…”
Section: Sensitivity Of Results To Computational Parameterssupporting
confidence: 91%
See 3 more Smart Citations
“…For cases olBα4 and olCα4, the agreement is within 5 dB Hz −1 . The reduction of the low-frequency slat noise with increasing angle of attack captured by the present simulations agrees with previous results in the literature (Dobrzynski & Pott-Pollenske 2001;Kolb et al 2007;Imamura et al 2009;Amaral et al 2017). Low-frequency sound amplitude, especially for the narrowband peaks, is reduced as the overlap is increased, to the point that the peaks are not observed for the largest overlap simulated, olCα4.…”
Section: Sensitivity Of Results To Computational Parameterssupporting
confidence: 91%
“…2009; Amaral et al. 2017). Low-frequency sound amplitude, especially for the narrowband peaks, is reduced as the overlap is increased, to the point that the peaks are not observed for the largest overlap simulated, .…”
Section: Unsteady Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pagani, Souza & Medeiros (2017) and Amaral et al. (2018) studied the effect of gap, overlap and slat deflection on the noise. They found that the narrowband peaks are relevant in the angle-of-attack range roughly between 0 and 12.…”
Section: Introductionmentioning
confidence: 99%